Perception on the Mandatory Use of Body Worn Cameras in Police Patrol Operation in Barangay Fairview Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A body worn camera is a device that is clipped to a police officer's chest that records audio andvideo footage that can be reviewed and used as evidence. This device is usually operated bypolice patrol officers when conducting their duties. This research is all about determining theunderlying factors regarding the perception of the community and police patrol officers in themandatory use of body-worn cameras.Based on the study, the police patrol officers and the community stated that the use of body-worn cameras during police operations eliminates uncertainty and increases transparency.Likewise, as long as the policies and guidelines are strictly adhered to, footage captured with abody-worn camera serves as reliable evidence in court. Body-worn cameras, on the otherhand, are difficult to conceal and easy to discharge during police operations. Similarly, policeofficers still rely on an alternative recording device during police operations, and there is still alack of body-worn cameras in all police stations. This study focuses on determining theperception of the community and police patrol officers of the mandatory use of body-worncameras.
Keywords: Criminology